Numerical simulation experiments and regression modeling for asperity contact of ceramic surfaces. (May 2021) - Tan, Yanqing; Li, Chengshun
Ceramic materials, with their excellent properties, have been widely used in the engineering field. With the ceramic surface as the research object, the properties of elastic contact of ceramic surfaces are studied using the numerical simulation calculation method. In this paper, uniform experimental design is carried out with topography parameters, external load, and material property parameters, which have a direct impact on the surface contact; a numerical calculation model is established and a series of simulation experiments is carried out on the contact of asperities on the ceramic surface, which not only intuitively shows the contact behavior of asperities on the ceramic surface, but also obtains the contact parameters of the surface. Then, the numerical simulation results are compared with those of G-W model, which proves the feasibility of the numerical simulation calculation and shows that the numerical simulation model established in this paper is more in line with the engineering practice than the G-W model. Through the regression analysis of the simulation results, the analytical calculation model between the surface contact parameters and the influencing factors is established, which provides references for quantitative analysis and characterization of contact properties related to the material surface.